CODE-SWITCHING: STUDY ON THE SPEECH OF INDONESIAN JAVANESE EDUCATED BILINGUALS - Sudarsono, Sudarsono (Lire Journal (Journal of Linguistics and Literature), 2021)
The present study aims to investigate the code-switching applied by educated bilinguals. It is a quantitative and qualitative study. The data were collected from the participants doing Master and doctoral degrees at several universities in Melbourne, Australia and their spouses. The data were sorted out of the corpora recorded from discussions, conversations, a monologue equivalent with 50,117 words of talks. They were recorded from natural speeches in natural settings. The data were analyzed and interpreted analytically. The research found out that the bilinguals code-switched in their speech at a system, not at random. The code-switching patterns were categorized into Single Lexical Code-switching, Phrasal Code-switching, Intra-sentential Code-switching, and Inter-sentential Code-switching. Bilinguals code-switched from the matrix language into the embedded language to show their communicative strategy, social-cultural values, and self-expression.